A Political Companion to Marilynne Robinson - Lane, Joseph H., Jr., 1968-; Mariotti, Shannon L. (Shannon Lee) (Book collections on Project MUSE., 2016)
Marilynne Robinson is arguably one of the most important writers of our time. Her voice resonates across the richly imagined American landscapes within which she grounds her stories of love and loss, alienation and belonging, injustice and redemption. Robinson's award-winning body of work -- including Gilead, winner of the 2005 Pulitzer Prize for Fiction and the National Book Critics Circle Award; Home, winner of the Orange Prize and the Los Angeles Times Book Prize; and Lila, winner of the National Book Critics Circle Award -- has cultivated admiration all over the world, offering readers new and profound interpretations of the meanings of transience, presence, convention, and resistance. In A Political Companion to Marilynne Robinson, Shannon L. Mariotti and Joseph H. Lane Jr. assemble both rising and established political theorists to explore the juxtaposition of Robinson's nonfiction works and her novels, and to examine their connections to contemporary political issues. The collection analyzes Robinson's writings on American democracy, community, and freedom, and it includes an engrossing interview with the author specifically conducted for this volume. From an exploration of the democratic potential in being a "housekeeper of homelessness" to a study of models of action against racial injustice, this volume provides fascinating new insights into Robinson's work and how it reflects and reassesses American political culture and theory